2018
DOI: 10.4178/epih.e2018031
|View full text |Cite
|
Sign up to set email alerts
|

Functional disorders of the lung and symptoms of respiratory disease associated with occupational inhalation exposure to wood dust in Iran

Abstract: OBJECTIVESThe possible adverse respiratory effects of airborne pollutants in sawmills have not been thoroughly investigated in Iran. Additionally, the extent to which workers are exposed to this organic dust and its associated bioaerosols has not been extensively quantified. Likewise, the predominant bacterial and fungal species associated with wood dust have not been characterized. The present study was undertaken to address these issues.METHODSOne hundred male individuals exposed to wood dust and 100 unexpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 40 publications
8
37
3
Order By: Relevance
“…This finding agrees with studies done among wood workers in Tanzania, Macedonia, Iran and Sweden [3,4,21,35]. The increased prevalence of phlegm and wheezing among particleboard workers in our study was also in compliance with the findings among parquet manufacturing workers in Macedonia and sawmill workers in Iran [3,4]. Furniture manufacturing workers in Thailand had an increased risk of wheezing and breathlessness compared to office workers [7,12] which is also consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding agrees with studies done among wood workers in Tanzania, Macedonia, Iran and Sweden [3,4,21,35]. The increased prevalence of phlegm and wheezing among particleboard workers in our study was also in compliance with the findings among parquet manufacturing workers in Macedonia and sawmill workers in Iran [3,4]. Furniture manufacturing workers in Thailand had an increased risk of wheezing and breathlessness compared to office workers [7,12] which is also consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed a higher prevalence of cough among particleboard workers than the controls. This finding agrees with studies done among wood workers in Tanzania, Macedonia, Iran and Sweden [3,4,21,35]. The increased prevalence of phlegm and wheezing among particleboard workers in our study was also in compliance with the findings among parquet manufacturing workers in Macedonia and sawmill workers in Iran [3,4].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations